Studi Hindcasting Dalam Menentukan Karakteristik Gelombang dan Klasifikasi Zona Surf Di Pantai Uluwatu, Bali - Santoso, Karina; Putra, I Dewa Nyoman Nurweda; Dharma, I Gusti Bagus Sila (Journal of Marine and Aquatic Sciences, 2018)
Bali is one of the islands where there are many surf zones with various characteristics. In addition, Bali is also a heaven with a classy wave for the surf ers of the world. One of the most challenging places to surf in Bali is Uluwatu Beach. Uluwatu Beach is ranked the 3rd best surf spot in the world version of CNN Travel in 2012. Wind causes sea wave s, therefore wind data can be used to estimate the height and direction of the wave s. Wave Hindcasting with Sverdrup, Munk and Bretschneider (SMB) method is calculated based on wind data for 10 years (2001 - 2010) from BMKG Ngurah Rai Station - Denpasar to obtain a significant wave height and period. In this research, it is necessary to approach through Hindcasting procedure, wave transformation analysis and surfing Terminology in determining the type of breaking wave and classification of surf zone in Uluwatu Beach area. Wave calculation result in Uluwatu Beach dominated by wave that coming from west side with significant wave height (Hs) of 0.98 m and significant wave period (Ts) of 5.21 s. The wave height due to the influence of wave refraction and shoaling is 0.976 m. The breaking wave height obtained from the calculation is 1.04 m at a depth of 0.849 m. From the result in this research, it can be concluded that the breaking wave type that occurred at Uluwatu Beach is plunging type according to the calculation result from its Irribaren number (0.4 <Ni <2.3). The classification of the surf zone at Uluwatu Beach based on its breakup type of wave is thought to be a good zone for surf ers on intermediate level.